Changes of the energetic profile in masters' swimmers over a season - Ferreira, M I (2020)
The aim of this study was to track and compare the changes of performance and energetic profile of male and female masters swimmers during a season. Eleven female (age: 34.7±7.3-y) and fourteen male (age: 35.6±7.4-y) with 4.2±3.7-y and 3.9±1.6-y of experience in masters, respectively, performed an all-out 200 m freestyle to evaluate total energy expenditure (Etot), aerobic (Aer), anaerobic lactic (AnL) and alactic (AnAl) contributions. The oxygen uptake (VO2) was measured immediately after the 200 m trial and the VO2 reached during the trial was estimated through the backward extrapolation of the O2 recovery curve. Fingertip capillary blood samples were collected before the 200 m trial and 3, 5, and 7 minutes after its end. Significant differences were observed between male (TP1:177.50±30.96s; TP2:174.79±29.08s; TP3:171.21±22.38s) and female (TP1:205.18±24.47s; TP2: 197.45±20.97s; TP3: 193.45±18.12s) for 200 m freestyle performance at the three time periods (TPs). Male presented higher Etot in all TPs (TP1:230.40±48.40kJ; TP2:242.49±37.91kJ; TP3:257.94±46.32kJ) compared with that found for female swimmers (TP1:188.51±35.13kJ; TP2:193.18±20.98kJ; TP3:199.77±25.94kJ). Male presented higher AnL (TP1:33.42±6.82kJ; TP2:30.97±8.73kJ; TP3:30.66±8.27kJ) and AnAl (TP1:30.61±3.48kJ; TP2:30.61±3.48kJ; TP3:30.60±3.48kJ) than female (TP1:18.83±8.45kJ; TP2:14.98±4.17kJ; TP3:18.33±8.66kJ) and (TP1:24.32±2.22kJ; TP2:24.31±2.23kJ; TP3: 24.31±2.23kJ). Aerobic metabolism is the major contributor for Etot both in male (TP1:71.63±4.99%; TP2:74.05±5.03%; TP3:76.14±4.46%) and female swimmers (TP1:76.87±3.86%; TP2:79.40±3.63%; TP3:78.40±5.54%). The better performance obtained by male compared to female swimmers may be due to the different contributions of the energetic pathways. Aerobic metabolism was the major contributor to Etot in a 200 m race, in both genders. Partial aerobic contribution was higher in female, while partial anaerobic contribution was greater in male.